Public law / by Mark Elliott and Robert Thomas - Elliott, Mark. (New Delhi, 2011)
Public Law is an advanced, high quality textbook that comprehensively covers the key topics found on undergraduate public law courses. The book presents a sophisticated and accessible analysis of the law and institutions of public law, and places the legal issues within the wider socio-political context within which the constitution operates. Three key themes that permeate the content allow students to approach the subject in a structured and easy to understand way, and questions posed throughout the chapters give students the opportunity to provide answers that show how their knowledge has increased as the chapter progresses. The key themes are: -The significance of executive power in the contemporary constitution and the challenge of ensuring that those who wield it are held to account; -The shift in recent times from a political to a more legal constitution and the implications of this change; -The increasingly 'multi-layered' character of the British constitution. Online Resource Centre Public Law is accompanied by a free, open-access Online Resource Centre (www.oxfordtextbooks.co.uk/orc/elliott_thomas) which offers the following resources to support students: - Figures from the book reproduced online - A list of useful websites for students - Regularly posted legal and political updates for the book - A testbank of questions for tutors to assess students' progress This book has been highly endorsed by lecturers for level of coverage, accuracy, and the manner in which the three themes provide an excellent backdrop to the book's content. 'I found the book impressive and likely to be of interest and use to a great many. It is written in a style that is pitched about the right level. It was easy to understand and provides - for me - a good blend of black letter law and socio-political context' - David Mead; University of East Anglia Written by two experienced public law scholars, Public Law is an essential new text that focuses on what students need to engage with and understand this challenging subject.
Keywords: Public law